2023
DOI: 10.1021/acscatal.2c05631
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Application of Bismuth LMCT Photocatalysis in Radical Coupling Reactions

Abstract: Ligand-to-metal charge transfer (LMCT) photocatalysis allows the activation and synthetic utilization of halides and other heteroatoms in metal complexes. Many metals are known to undergo LMCT but so far remain underutilized in the field of catalysis. A screening assay identifying LMCT activity helped us to expand this catalysis concept to the application of bismuth LMCT in organic radical coupling reactions. We demonstrate its application for the generation of two different radicals (chlorine and carboxyl) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 69 publications
2
31
0
1
Order By: Relevance
“…In recent years, several metal-catalysed reactions other than oxygenation that are initiated by HAT from C-H bonds to chlorine radicals have been reported. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] 2.1.1 Iron(III) chloride. Imoto et al first reported the photocatalysis of FeCl 3 in the oxidation of ethylene glycol derivatives [44][45][46] and benzylic chlorination of toluene; the effect of water on this reaction was subsequently reported.…”
Section: Metal Chloridesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several metal-catalysed reactions other than oxygenation that are initiated by HAT from C-H bonds to chlorine radicals have been reported. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] 2.1.1 Iron(III) chloride. Imoto et al first reported the photocatalysis of FeCl 3 in the oxidation of ethylene glycol derivatives [44][45][46] and benzylic chlorination of toluene; the effect of water on this reaction was subsequently reported.…”
Section: Metal Chloridesmentioning
confidence: 99%
“…In recent years, several metal-catalysed reactions other than oxygenation that are initiated by HAT from C–H bonds to chlorine radicals have been reported. 29–43…”
Section: Chlorine-radical-mediated C–h Oxygenation Reactionsmentioning
confidence: 99%
“…Moreover, various electron-deficient alkenes and di- tert -butyl azodicarboxylate were demonstrated to be capable radical acceptors for this catalytic manifold. Analogous LMCT strategies employing other homoleptic metal–chloride complexes, including iron, 97–100 titanium, 101 and bismuth, 102 have also been recently reported (Scheme 3B).…”
Section: Transformations Mediated By Halogen Radicalsmentioning
confidence: 99%
“…20 The couplings of arylboronic acids were reported using organobismuth(III) species, and Bi(III)/ Bi(V) redox cycles were proposed for these reactions. 21−23 Recently, an aminooxygenation reaction 24 and a photoreaction 25 were developed using a BiCl 3 catalyst, which is an inorganic bismuth(III) compound. Nevertheless, further development of catalytic reactions using nontoxic Bi compounds is essential.…”
mentioning
confidence: 99%
“…Triphenylbismuth, an organobismuth­(III) compound, behaves as a redox catalyst in the presence of a terminal oxidant in the oxidative cleavage of 1,2-diols and in the oxidation of hydrazones . The couplings of arylboronic acids were reported using organobismuth­(III) species, and Bi­(III)/Bi­(V) redox cycles were proposed for these reactions. Recently, an aminooxygenation reaction and a photoreaction were developed using a BiCl 3 catalyst, which is an inorganic bismuth­(III) compound. Nevertheless, further development of catalytic reactions using nontoxic Bi compounds is essential.…”
mentioning
confidence: 99%